The Process of Self Acceptance as Portrayed in The Substance Film (2024) by Coralie Fargeat - Rani Puspita (English Language, Linguistics, Literature, And Education Journal, 2025)
Self-acceptance is the ability to acknowledge and embrace both strengths and weaknesses without self-judgment. This study analyzes the process and effects of self-acceptance portrayed in Coralie Fargeat’s The Substance using a literary psychology approach with a qualitative descriptive method. The analysis applies Kübler-Ross’s (1973) five stages of grief to explain the self-acceptance process of the main character and Najwa Zebian’s (2016) concept to examine its effects. Data were collected through documentation of film dialogues representing self-acceptance. The findings show that the process follows the stages of denial, anger, bargaining, depression, and acceptance. The effects are reflected in internal peace and happiness, improved mental health, career, and relations. The film emphasizes the importance of authenticity and critiques social pressures and beauty standards that compel individuals, especially women, to sacrifice their true selves to meet idealized appearances, encouraging the courage to remain authentic despite societal demands.